A Novel Design for Decision Rules Based on Statistical Testing Strategies of Binary Endpoints in a Definitive Go/No-Go Single-Treatment Clinical Study. (May 2014) - Zhou, Ming; Shen, Larry Z.
In drug development, a definitive go/no-go clinical study is sometimes conducted before major investment is made to advance the development into the next stage. Such a study sometimes focuses on a key binary endpoint, such as a particular adverse event, treatment failure, or device problem. However, such a study is often constrained by budget and scope, which limit the sponsor's ability to draw clear conclusions. This paper proposes a novel design that uses Wilson confidence intervals to devise statistical testing strategies that allow the decision makers to arrive at certain definite conclusions within the constraint of the study's scope.